The Effectiveness of Sump Dimension Design: A Case Study in Nickel Mining - Excellentia Riane Kapugu; A.A. Inung Arie Adnyano; Rizqi Prastowo; Akhmad Zamroni; Manmeet Kaur; Nameeta Brahme (CV FOUNDAE, 2022)
The presence of water in mining activities is common, especially in tropical areas that have high rainfall, such as the research location at PT ANTAM Maluku Utara at the Moronopo Site. While the sump maintenance needs to be considered so that the sump can accommodate the incoming discharge. The purpose of this research is to calculate the total discharge entering the mine and to design the dimensions of the sump according to the incoming water discharge. The research method used is the Gumbel method starting from the analysis of rainfall data at the research location starting in 2004-2013 and then continuing with 2019-2020 data, the planned rainfall value is 96.56 mm/day, rainfall intensity is 15.63 mm/day hours with a rain return period of 25 years and a hydrological risk of 18.46 % and the total inflow of mine water is 17,556 m3/hour. After calculating the sump capacity in the Danis 2 area, it still has not accommodated the incoming discharge with the remaining unaccommodated discharge of 2,319.1 m3/hour.